A Multi-Factor Biometric Authentication Framework to User for Securing Digital Transaction (International Journal of Engineering and Computer Science, 2023)
The recent growth of digital transactions over the internet is high. This is the newest topic which is to be implemented as well as need to study related with the security.  The development of technology we need to improve and build the safe authentication scheme over the internet. The safe authentication scheme is protecting the user valuable information against security threats. While performing digital transactions over the internet, the protection is turn into high importance and demand for authentication is more necessary than before.  In the traditional authentication there are so many problems such as username, password & so on. Also, intruders will crack various ways of hacking user information, passwords including brute force attack, shoulder surfing, dictionary attacks, etc.This paper is useful to performing a secure authentication scheme using different fusion techniques for digital transactions. The propose system approach here combines user details as like user name, password, OTP and biometrics (traits as like fingerprint, face & iris) fusion verification for a more valid user authentication. Our proposed point of view has been initiating to improve security benefits for various forms of invasion & authentication layers turn on password-based attacks.